Collaborating with Teachers and Students in Multiliteracies Research: "Se hace camino al andar" - McClay, Jill Kedersha (Alberta Journal of Educational Research, 2006)
Multiliteracies theory, with an emphasis on literacy as diverse and negotiated social practices involving multimodal work, is particularly compatible with collaborative research, as such research enables researchers and teachers to consider students’ multiple perspectives and intentions for their work. This article discusses three collaborative teacher-researcher case studies of teaching and learning in a multiliteracies framework with middle-years students. In these case studies teachers developed literacy projects that explicitly sought to capitalize on students’ out-of-school literacy interests and practices. Collaborative researcher-teacher relationships enabled comfortable research relationships with students throughout 6- to 10-week instructional projects; students’ perspectives throughout the projects enriched both the teaching and the research. These case studies suggest implications regarding collaborative relationships and stances among researchers, teachers, and students.